Drivers for Performance in Innovative Research Groups: The Mediating Role of Transactive Memory System. Issue 3 (July 2018) - Cabeza-Pullés, Dainelis; Gutierrez-Gutierrez, Leopoldo J.; Llorens-Montes, F.J.
This article contributes to research on transactive memory systems (TMSs) by analyzing the relationship between trust, collective mind (CM), and network ties (NT) as antecedents of performance in innovative university research (IUR), and the mediating role of the TMS in these relationships. The conceptual model grounded in seven hypotheses is tested through structural equations modeling. The data analyzed are drawn from 257 directors Spanish university research groups. The results show that TRUST, CM, and NT are positively related to the TMS and that the TMS is positively related to IUR. The most striking result is that the TMS mediates the relationships of TRUST, CM, and NT to IUR, becoming a necessary condition for TRUST, CM, and NT to improve IUR. These results support the conclusion that managers of university research groups should promote the development of TMSs to stimulate IUR in order to make these groups more competitive.